Beer Brewing in Namibia and Sensory Profile of Beer on Sale in the Namibian Market. (2nd January 2023) - Donadini, Gianluca; Spigno, Giorgia
Abstract: This study presents a brief history of beer in Namibia and explores the Namibian beer market by investigating the sensory characteristics of the beers readily available on the off-premises segment of the drink market. Twenty-two beers were sampled, and their characteristics were quantified using Descriptive Analysis and trained assessors. The results showed that the beers under study included a small range of products in terms of beer styles, most of the beers brewed in or imported to Namibia being bottom-fermented blond lagers of low to moderate alcohol content. These beers were not typically complex and divided into samples brewed in accordance with the Reinheitsgebot standards and into samples brewed in accordance to brewing protocols not compliant with the Germany purity law. Although sameness seemed to be the keyword, subtle significant differences existed among these beers. Some samples, the most flavorsome overall, were perceived as being significantly more alcoholic, bodied, carbonated, bitter, astringent, malty, and richer in solvent-like and vinous impressions. Other samples were perceived as having a thinner mouthfeel and being richer in caramel-like and cooked vegetable notes. Other blond beers included lite beers and were identified as thinner, whereas alcohol-free beers were identified as watery, rich in wort and cooked vegetable-like notes, and low in bitterness and perceived levels of carbonation. IPA and Doppelbock stood out from the others due to maltiness, bitterness, fruitiness, and a full body. Nearly all the samples were free from faults, and this attested to the high-quality standards of Namibian beers. In terms of brewing styles, unfilled gaps in the market exist and offer untapped opportunities for brewers.